UNDERSTANDING ADVERBS: THEIR FUNCTIONS AND GRAMMATICAL CATEGORIES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of adverbs, focusing on theirgrammatical categories and syntactic functions. It begins by defining adverbs as wordsthat modify verbs, adjectives, other adverbs, and entire clauses, outlining their role inconveying nuances of time, manner, frequency, degree, and certainty. The article thencategorizes adverbs semantically (based on meaning), morphologically (based onformation), and syntactically (based on sentence position), illustrating their versatility in